Unveiling the role of KSHV‐infected human mesenchymal stem cells in Kaposi's sarcoma initiation - Lacunza, Ezequiel (2024)
Kaposi´s sarcoma (KS) may derive from Kaposi´s sarcoma herpesvirus (KSHV)‐ infected human mesenchymal stem cells (hMSCs) that migrate to sites characterized by inflammation and angiogenesis, promoting the initiation of KS. By analyzing the RNA sequences of KSHV‐infected primary hMSCs, we have identified specific cell subpopulations, mechanisms, and conditions involved in the initial stages of KSHV‐ induced transformation and reprogramming of hMSCs into KS progenitor cells. Under proangiogenic environmental conditions, KSHV can reprogram hMSCs to exhibit gene expression profiles more similar to KS tumors, activating cell cycle progression, cytokine signaling pathways, endothelial differentiation, and upregulat- ing KSHV oncogenes indicating the involvement of KSHV infection in inducing the mesenchymal‐to‐endothelial (MEndT) transition of hMSCs. This finding underscores the significance of this condition in facilitating KSHV‐induced proliferation and reprogramming of hMSCs towards MEndT and closer to KS gene expression profiles, providing further evidence of these cell subpopulations as precursors of KS cells that thrive in a proangiogenic environment.